Implementasi Enkripsi Dekripsi Paket Data pada Rancang Bangun Smart Home Menggunakan Protokol MQTT - Sari, Risna; -, Ayu Rosyida Zain; Marta Surya Cakraningrat (MULTINETICS, 2022)
Internet of Things (IoT) technology can be applied in many ways, one of which is home automation or Smart Home. There are several sensors and actuator modules in the Smart Home system such as movement sensors (PIR) to detect the presence of living things around the house, radio wave frequency-based authentication sensors (RFID) to ensure that only registered residents can enter the house, actuator servo actuator (SG90) which is used to open the door, and actuator switch (Relay) to automatically turn off the lights. All activities at home that apply the Smart Home concept can be done automatically without touching it directly by using a special application called SUSAH v2, which is an Android-based application created using MIT App Inventor. What is still a concern is the lack of the Smart Home system where the network usInternet of Things (IoT) technology can be applied in many ways, one of which is home automation or Smart Home. There are several sensors and actuator modules in the Smart Home system such as movement sensors (PIR) to detect the presence of living things around the house, radio wave frequency-based authentication sensors (RFID) to ensure that only registered residents can enter the house, actuator servo actuator (SG90) which is used to open the door, and actuator switch (Relay) to automatically turn off the lights. All activities at home that apply the Smart Home concept can be done automatically without touching it directly by using a special application called SUSAH v2, which is an Android-based application created using MIT App Inventor. What is still a concern is the lack of the Smart Home system where the network used is still a LAN and can only be controlled if the user is on the same network as the Smart Home system. Therefore, this research objective is to developing, testing, and implementing security using cryptographic methods and the integration of the Antares Platform based on the MQTT protocol to be able to make the Smart Home system accessible on a WAN anywhere and anytime, taking into account the security of the data information sent. To create an IoT-based Smart Home system that is more efficient and remains safe when used.ed is still a LAN and can only be controlled if the user is on the same network as the Smart Home system. Therefore, this research objective is to developing, testing, and implementing security using cryptographic methods and the integration of the Antares Platform based on the MQTT protocol to be able to make the Smart Home system accessible on a WAN anywhere and anytime, taking into account the security of the data information sent. To create an IoT-based Smart Home system that is more efficient and remains safe when used.